2017
DOI: 10.7554/elife.22904
|View full text |Cite
|
Sign up to set email alerts
|

MCTP is an ER-resident calcium sensor that stabilizes synaptic transmission and homeostatic plasticity

Abstract: Presynaptic homeostatic plasticity (PHP) controls synaptic transmission in organisms from Drosophila to human and is hypothesized to be relevant to the cause of human disease. However, the underlying molecular mechanisms of PHP are just emerging and direct disease associations remain obscure. In a forward genetic screen for mutations that block PHP we identified mctp (Multiple C2 Domain Proteins with Two Transmembrane Regions). Here we show that MCTP localizes to the membranes of the endoplasmic reticulum (ER)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 69 publications
0
55
0
Order By: Relevance
“…4A). MCTP2 is an 878 amino acid ER resident protein with a membrane embedded regions containing the RHD near the Cterminus and three C2 domains 27,28 . MCTP proteins are conserved in higher eukaryotes.…”
mentioning
confidence: 99%
“…4A). MCTP2 is an 878 amino acid ER resident protein with a membrane embedded regions containing the RHD near the Cterminus and three C2 domains 27,28 . MCTP proteins are conserved in higher eukaryotes.…”
mentioning
confidence: 99%
“…The majority of recent studies about synaptic homeostasis at the Drosophila NMJ have emphasized that presynaptic adjustments to neurotransmitter release properties must occur within minutes of drug-induced (PhTox) postsynaptic receptor inhibition in order to induce a rapid and offsetting response to PhTox challenge. Important presynaptic parameters uncovered through these studies include regulation of presynaptic Ca 2+ influx (Frank et al, 2006; Frank et al, 2009; Müller and Davis, 2012; Wang et al, 2014; Wang et al, 2016a; Younger et al, 2013); regulation of the size of the readily releasable pool (RRP) of presynaptic vesicles (Harris et al, 2015; Müller et al, 2015; Müller et al, 2012; Wang et al, 2016a; Weyhersmüller et al, 2011); control of SNARE-mediated fusion events (Dickman and Davis, 2009; Dickman et al, 2012; Müller et al, 2011); control of neuronal excitability (Bergquist et al, 2010; Parrish et al, 2014; Younger et al, 2013); and recently, ER calcium-sensing downstream of presynaptic calcium influx (Genç et al, 2017). For almost all of the cases in which a mutation or an experimental condition blocks the short-term induction of homeostatic signaling, the same perturbation has also proven to block its long-term maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it was found that release at NMJs undergoing PHP is more sensitive to EGTA-AM, and that EGTA-sensitive vesicles are required for PHP (Wentzel et al, 2018) (but see Genç et al, 2017). This implies that loosely coupled vesicles have to be recruited in addition to tightly coupled vesicles to potentiate release during PHP (see also paragraph "Proteostasis").…”
Section: Physiology and Genesmentioning
confidence: 99%